Chemical Composition, Physicochemical Characteristics, and Nutritional Value of Lannea kerstingii Seeds and Seed Oil - Judicaël Thomas Ouilly; Patrice Bazongo; Adjima Bougma; Nèbpawindé Kaboré; Anne Mette Lykke; Amadé Ouédraogo; Imaël Henri Nestor Bassolé (Journal of Analytical Methods in Chemistry)
The chemical composition, main physicochemical properties, and nutritional value of seed flour and seed oil of Lannea kerstingii were studied. The results indicated that seeds contained 3.61% moisture, 57.85% fat, 26.39% protein, 10.07% carbohydrates, and 2.08% ash. Potassium was the predominant mineral, followed by magnesium and calcium. The essential amino acids were at higher levels than the estimated amino acid requirements of FAO/WHO/UNU except for lysine. Fatty acid composition showed that oleic acid was the major fatty acid, followed by palmitic, linoleic, and stearic acids. Physicochemical properties of the seed oil were melting point, 19.67°C; refractive index (25°C), 1.47; iodine value, 60.72/100 g of oil; peroxide value, 0.99 meq. O2/kg of oil; p-anisidine value, 0.08; total oxidation (TOTOX) value, 2.06; oxidative stability index (120°C), 52.53 h; free fatty acids, 0.39%; acid value, 0.64 mg of KOH/g of oil; saponification value, 189.73. Total amount of tocopherols, carotenoids, and sterols was 578.60, 4.60, and 929.50 mg/kg of oil, respectively. γ-Tocopherol (82%), lutein (80%), and β-sitosterol (93%) were the most abundant forms of tocopherols, carotenoids, and sterols, respectively. Seeds of L. kerstingii constitute an alternative source of stable vegetable oil and protein for nutritional and industrial applications.